2001
DOI: 10.1152/jappl.2001.90.1.321
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human pregnancy on cardiac autonomic function above and below the ventilatory threshold

Abstract: This study examined the effects of human pregnancy on heart rate variability (HRV), spontaneous baroreflex (SBR) sensitivity, and plasma catecholamines at rest and during exercise. Subjects were 14 healthy, physically active pregnant women (PG; mean gestational age = 33.9 +/- 1.0 wk). Results were compared with an age-matched nonpregnant control group (NPG; n = 14) with similar characteristics. The electrocardiographic R-wave-R-wave interval and systolic blood pressure (via finger plethysmograph) were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
67
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 35 publications
5
67
0
3
Order By: Relevance
“…The progressive increase in PEF after 14-16 weeks of gestation is in concordance with previously reported bronchodilatation occurring during pregnancy. 28 The physiological mechanisms of bronchodilatation in pregnancy remain unclear, but pregnancy-induced reduction in pulmonary vagal efferent activity, 29 and progesterone-mediated alteration in airway smooth muscle tone, [30][31][32] may separately or in combination be responsible.…”
Section: Discussionmentioning
confidence: 99%
“…The progressive increase in PEF after 14-16 weeks of gestation is in concordance with previously reported bronchodilatation occurring during pregnancy. 28 The physiological mechanisms of bronchodilatation in pregnancy remain unclear, but pregnancy-induced reduction in pulmonary vagal efferent activity, 29 and progesterone-mediated alteration in airway smooth muscle tone, [30][31][32] may separately or in combination be responsible.…”
Section: Discussionmentioning
confidence: 99%
“…The latter was shown to be an interesting stress indicator (Nater et al, 2005;Rohleder, Nater, Wolf, Ehlert, & Kirschbaum, 2004). Women at the beginning of the second and third trimesters of their pregnancy were assessed, based on the knowledge that there are differences in physiological baseline levels and stress responses (Avery, Wolfe, Amara, Davies, & McGrath, 2001;Mastorakos & Ilias, 2003;Nierop et al, 2006;Petraglia et al, 2001;Wang, Zhang, & Zhao, 1999), as well as evidence of differences in psychological stress responses (Glynn, Wadhwa, Dunkel-Schetter, Chicz-Demet, & Sandman, 2001;Paarlberg et al, 1999) at different stages of pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have assessed the site(s) within the baroreflex arc that are functionally depressed. Initial studies documented depressed baroreflex control of multiple efferents, including heart rate (5,21,24,123,175,193), renal and muscle sympathetic nerve activity (79,89,148,149), and hormones such as vasopressin and ACTH/glucocorticoids (26,104). Multiple approaches have been used to assess the effect of pregnancy on reflex control of the autonomic nervous system (for reviews, see Refs.…”
mentioning
confidence: 99%
“…Pharmacological blockade of the sympathetic or parasympathetic nervous systems has revealed that the sympathetic contribution to heart rate baroreflex curves is particularly blunted (21,123). In addition, pregnancy-induced decreases in baroreflex function in humans and rats have been successfully detected via measurement of spontaneous baroreflex sensitivity, which identifies brief spontaneous baroreflexmediated ramps in which systolic pressure and pulse interval both simultaneously increase or decrease (5,24,175,193). This measurement is restricted to the more linear segment of baroreflex curves close to basal values and highlights in particular the impact of rapid changes in parasympathetic control of the heart, documenting that pregnancy depresses these aspects of baroreflex function as well.…”
mentioning
confidence: 99%